AI INTEGRATION IN GOVERNMENT NUTRITION PROGRAMS: A SUSTAINABLE DEVELOPMENT APPROACH FOR HILLY REGIONS OF UTTARAKHAND - Dr. Amar Nath Taram (International Educational Journal of Science and Engineering, 2025)
Malnutrition remains a critical challenge in the hilly regions of Uttarakhand due to geographical isolation, seasonal inaccessibility, and fragmented service delivery within government nutrition programs such as ICDS and POSHAN Abhiyaan. Integrating Artificial Intelligence (AI) offers transformative solutions by enabling predictive analytics for supply chains, real-time malnutrition surveillance, and personalized nutrition counseling in local dialects. AI-powered tools like computer vision-based growth monitoring and chatbots can improve early detection of stunting and wasting by 20–30% and reduce stock-outs of nutritional supplements by 40%. Case studies from Kenya, Nepal, and Indian states like Madhya Pradesh demonstrate measurable improvements in maternal dietary diversity, program accountability, and cost efficiency through AI integration. Aligning with Sustainable Development Goals (SDGs 2, 3, 5, and 10), AI-driven nutrition interventions can enhance maternal and child health, empower frontline workers, and build a resilient, inclusive ecosystem for remote hill communities.